2014
DOI: 10.1007/s10930-014-9572-z
|View full text |Cite|
|
Sign up to set email alerts
|

Conformational Transition Pathway in the Inhibitor Binding Process of Human Monoacylglycerol Lipase

Abstract: Human monoacylglycerol lipase (MGL) catalyzes the hydrolysis of 2-arachidonoylglycerol to arachidonic and glycerol, which plays a pivotal role in the normal biological processes of brain. Co-crystal structure of the MGL in complex with its inhibitor, compound 1, shows that the helix a4 undergoes large-scale conformational changes in response to the compound 1 binding compared to the apo MGL. However, the detailed conformational transition pathway of the helix a4 in the inhibitor binding process of MGL has rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The C α atoms distance between the lid domain residues Phe-159 (helix α4) and Gly-210 (helix α6) may be used as a sensitive probe to analyze access to the hMGL active site 40 . The 14.7 Å distance is indicative of a fully open conformation, whereas a distance of 7.8 Å is indicative of a closed conformation.…”
Section: Resultsmentioning
confidence: 99%
“…The C α atoms distance between the lid domain residues Phe-159 (helix α4) and Gly-210 (helix α6) may be used as a sensitive probe to analyze access to the hMGL active site 40 . The 14.7 Å distance is indicative of a fully open conformation, whereas a distance of 7.8 Å is indicative of a closed conformation.…”
Section: Resultsmentioning
confidence: 99%
“…In this article, we have shown that more accurate positioning can be achieved using Δ‐distance mapping. This established method could have wide applicability as more conformational state data become available. The majority of the TMS segments, including TMS11, which display intradomain movement, independent of the two domains' alternating access movement, were found in close proximity to the interdomain linker helices.…”
Section: Discussionmentioning
confidence: 99%
“…In this article we use an established technique, Δ‐distance mapping, to compare structures in different conformational states. The concept of calculating Δ‐distance maps is not new, but the recent availability of multiple conformational states for MFS homologs, LacY and XylE, has created a new application area. In fact, the most recent version of Chimera, release 1.10, contains a new function called RR distance maps.…”
Section: Introductionmentioning
confidence: 99%
“…The nudged elastic band (NEB) method, developed as a chainof-states approach, has been demonstrated to be an effective algorithm for investigating the pathways involved in the dynamic process of ligands access and binding (Bergonzo et al, 2011;Lu et al, 2014;Xing et al, 2019) as well as conformational changes of proteins in different states (Chen et al, 2014;Li et al, 2014). In NEB, a transition path is approximated with a string of images (or copies) of the system.…”
Section: Partial Nudged Elastic Band (Pneb) Simulationsmentioning
confidence: 99%